2011
DOI: 10.1007/s10695-011-9466-3
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study on the effects of a pesticide (cypermethrin) and two metals (copper, lead) to serum biochemistry of Nile tilapia, Oreochromis niloticus

Abstract: The present study was designed to compare the responses in freshwater fish Oreochromis niloticus exposed to a synthetic pyrethroid, cypermethrin (CYP); an essential metal, copper (Cu); and a nonessential metal, lead (Pb). Fish were exposed to 0.05 μg/l CYP, 0.05 mg/l Cu, and 0.05 mg/l Pb for 4 and 21 days, and the alterations in serum enzyme activities, metabolite, and ion levels were determined. Alanine aminotransferase (ALT) and aspartate aminotransferase (AST) activities increased in response to CYP, Cu, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

17
89
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 231 publications
(119 citation statements)
references
References 47 publications
(56 reference statements)
17
89
0
Order By: Relevance
“…Accordingly, glycogen of liver is broken down (glycogenolysis) to meet the energy demand raised during cypermethrin stress, resulting in the reduction of hepatic glycogen content. On the other hand, an increase in plasma glucose level due to cypermethrin treatment, as observed in the present study, has also been observed on H. fossilis (Saha and Kaviraj 2009b) and O. niloticus (Firat et al 2011) probably due to an increase in hepatic glucose-6-phosphatase activity which enhances glycogenolysis and glucose synthesis from extrahepatic tissue proteins and amino acids (Firat et al 2011). Gluconeogenesis is another pathway to increase plasma glucose level during the stress of pesticide to fish (Saravanan et al 2011).…”
Section: Biochemical Parameterssupporting
confidence: 82%
See 1 more Smart Citation
“…Accordingly, glycogen of liver is broken down (glycogenolysis) to meet the energy demand raised during cypermethrin stress, resulting in the reduction of hepatic glycogen content. On the other hand, an increase in plasma glucose level due to cypermethrin treatment, as observed in the present study, has also been observed on H. fossilis (Saha and Kaviraj 2009b) and O. niloticus (Firat et al 2011) probably due to an increase in hepatic glucose-6-phosphatase activity which enhances glycogenolysis and glucose synthesis from extrahepatic tissue proteins and amino acids (Firat et al 2011). Gluconeogenesis is another pathway to increase plasma glucose level during the stress of pesticide to fish (Saravanan et al 2011).…”
Section: Biochemical Parameterssupporting
confidence: 82%
“…Reduced activities of hepatic alkaline phosphatase may lead to the breakdown of glycogen in order to get necessary energy to overcome the stress. Some researchers reported increased activities of alkaline phosphatase in the serum of fish exposed to cypermethrin, which might be due to the efflux of enzymes from the liver into bloodstream (Firat et al 2011;Meenambal et al 2012). On the other hand, the activity of acid phosphatase was elevated in cypermethrin-exposed O. niloticus as compared to control.…”
Section: Biochemical Parametersmentioning
confidence: 99%
“…This is consistent with the findings of Bernard and Grazyna (1999) and Firat et al (2011) whose studies showed that plasma K + levels actually increased in fish following exposure to heavy metals and pesticides The excessive accumulation of K + in the plasma of exposed fish could be an indication of renal disturbance in this fish, since K + is normally excreted by the kidneys.…”
Section: Discussionsupporting
confidence: 92%
“…This may be an indication that this exposure concentration (2 mg/L Pb) is too low to elicit such physiological disturbance in this fish. Firat et al (2011) showed that exposure of Nile Tilapia to even a lower concentration of Pb (0.05 mg/L Pb) did cause a significant reduction in the levels of plasma Na + and Cl − although this effect was observed during longer exposure periods It may therefore be inferred that C. gariepinus is not as sensitive to environmental contamination as other surrogate fish species. However, caution must be taken before generalizing that C. gariepinus is not as sensitive to environmental contamination as other surrogate fish species since the current study followed an acute exposure; the result could be quite different if the experiment followed a chronic exposure.…”
Section: Discussionmentioning
confidence: 98%
“…The amino transfer enzymes like ALT, ALP and creatinine are biochemical indicators in diagnosis of fish diseases and the increase in their activity is indicator of tissue damage due to toxic material (Firat et al 2011). The result of this study showed no difference of these biomarkers after 24 h in the all treatment with nZnO, CuSO4 separately and both of them together compared with the control.…”
Section: Discussionmentioning
confidence: 56%